Optical Fiber Communication Conference/National Fiber Optic Engineers Conference 2011 2011
DOI: 10.1364/ofc.2011.otho7
|View full text |Cite
|
Sign up to set email alerts
|

Performance prediction for WDM PM-QPSK transmission over uncompensated links

Abstract: We derive closed-form expressions depending on a single fitting parameter for performance prediction of WDM PM-QPSK long-haul uncompensated transmission. Besides general properties, we demonstrate that nonlinear penalty is always equal to 1.76 dB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 5 publications
3
41
0
Order By: Relevance
“…where ζ in = D in /D is the coordinate after which a dispersion of D in has been cumulated 3 . With the change of variables…”
Section: B Homogeneous Multi-spanmentioning
confidence: 99%
See 2 more Smart Citations
“…where ζ in = D in /D is the coordinate after which a dispersion of D in has been cumulated 3 . With the change of variables…”
Section: B Homogeneous Multi-spanmentioning
confidence: 99%
“…The distinctive feature of these highly dispersive systems is a Gaussian distribution of the received sampled signal [1], [2], a consequence of the addition of very many comparable-size nonlinear field interferers from symbol times even far away from the symbol of interest. The Gaussian nature of both the nonlinear interference (NLI) and the amplified spontaneous emission noise fields brings the theory of these nonlinear optical coherent communication systems back to the standard additive Gaussian noise (GN) model of most nonoptical telecommunications literature, and allows elementary system optimization rules based on the electrical signal to noise ratio [3]- [5].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…nonlinear signal propagation, the optimum OSNR is 13.77dB and 16.78dB when TX P is -2.44dBm and 0.5 dBm considering 16GBaud and 32GBaud respectively. For the result's confirmation, it is found that the optimum penalty between linear and nonlinear propagation is around 1.76dB [21]. It is also confirmed that the lines overlap for 16GBaud and 32GBaud respectively considering linear propagation.…”
Section: Optimization Of Osnr For Cotsmentioning
confidence: 51%
“…This nonlinear noise can be described as a Gaussian noise [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], at least in dispersion uncompensated (DU) coherent systems. Gaussian nature of the nonlinear interference (NLI) noise fields is conditioned by Gaussian distribution of the information sampled signal [4][5][6][14][15][16].…”
Section: Introductionmentioning
confidence: 99%